2000
DOI: 10.1590/s1516-89132000000400011
|View full text |Cite
|
Sign up to set email alerts
|

Gills scanning images of the seawater fish Eugerres brasilianus (Gerreidae)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 7 publications
8
10
0
Order By: Relevance
“…The present investigation observed that there is no angle between the two parts of the gill arch; epibranchials and ceratobranchials, the similar observation was observed by Hossler et al (1979) and Eiras-Stofella et al However, the most common in all teleost fish is the presence of a clear angle as noted in many literatures (Eiras-Stofella & CharvetAlmeida, 1997;Eiras-Stofella & Charvet-Almeida, 1998, 2000Kumari et al, 2005;Alsafy).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present investigation observed that there is no angle between the two parts of the gill arch; epibranchials and ceratobranchials, the similar observation was observed by Hossler et al (1979) and Eiras-Stofella et al However, the most common in all teleost fish is the presence of a clear angle as noted in many literatures (Eiras-Stofella & CharvetAlmeida, 1997;Eiras-Stofella & Charvet-Almeida, 1998, 2000Kumari et al, 2005;Alsafy).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, in freshwater fish Prochilodus scrofa Steindachner and in seawater Eugerres brasilianus, the gill filaments are shorter on both extremities of gill arch and in the strong curvature angle region (Eiras-Stofella & Charvet-Almeida, 1998, 2000, however, Kumari et al, (2012) in catfish and Carp reported that, the length of the gill filaments is shorter on one side than on the other corresponding side of the gill arch.…”
Section: Discussionmentioning
confidence: 97%
“…Our results revealed that L. sceleratus gills were characterized by a somewhat clear angle of curvature at the union of short epibranchials and long ceratobranchials as reported in many literatures (Eiras-Stofella & CharvetAlmeida, 1998, 2000Kumari et al, 2005;Alsafy), in contrast, there are some species that were characterized by the absence of this angle as noted by (Hossler et al, 1979;. However, other types of fishes exhibit an acute angle of curvature, almost in the middle of the gill arches like that found in freshwater fish Hypostomus eommersollii Val (Eiras-Stofella & Charvet-Almeida, 1997).…”
Section: Discussionsupporting
confidence: 85%
“…Many authors reported that the gill chamber of most teleost fish was bounded laterally by the operculum which closing the ventrolaterally opened gill opening which different in its position and mechanism of action (Eiras-Stofella & Charvet- Almeida, 1997Almeida, , 2000Alsafy, 2013;Elsheikh, 2013). Our finding noted that, the gill cavity was bounded laterally by a three layered gill covering which consisting of; outer cutaneous layer and the middle bony supportive layer while the third internal layer is a muscular layer.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation